Quality of life in children with severe forms of idiopathic nephrotic syndrome in stable remission—A cross‐sectional study. (15th July 2019) - Roussel, Aphaia; Delbet, Jean‐Daniel; Micheland, Laurianne; Deschênes, Georges; Decramer, Stephane; Ulinski, Tim
Abstract: Aim: Severe forms of idiopathic nephrotic syndrome (INS) require immunosuppressive therapy: oral treatment or intravenous therapy (rituximab, RTX). The main objective was to describe quality of life (QOL) in these specific patients. Methods: Cross‐sectional, multicentre, observational study analysed QOL using a standardised questionnaire in children from 7 to 17 years, with a steroid‐dependent or steroid‐resistant INS in stable remission. The questionnaire consisted of 30 questions concerning physical and emotional well‐being, self‐esteem, family, friends, school and disease resulting in a global score of 0‐100. Results: A total of 110 patients with a mean age of 11.6 years from three French paediatric nephrology centres were included. A total of 71 patients had oral immunosuppressive treatment, 27 had RTX, and 12 had both. 13.6% of patients had a steroid‐resistant INS. The mean number of relapses was 5.8. Seventy‐eight patients answered the questionnaire. The global score in the whole study population was 74.7; 72.6 in the RTX group, 76.2 in the oral drugs group, ( P  = 0.49). The results of sub‐dimension 'school' were statistically lower in RTX group (61.6 ± 19.5) compared with oral drugs group (71.4 ± 16; P  = 0.02). Conclusion: Global QOL score was high in 'difficult‐to‐treat' patients with INS in stable remission on oral immunosuppressive or RTX treatment.